Numerical simulation of an adobe wall under in-plane loading - Tarque, Nicola (2014)
Adobe is one of the oldest construction materials that is still used in many seismic countries, and different construction techniques are found around the world. The adobe material is characterized as a brittle material; it has acceptable compression strength but it has poor performance under tensile and shear loading conditions. Numerical modelling is an alternative approach for studying the nonlinear behaviour of masonry structures such as adobe. The lack of a comprehensive experimental database on the adobe material properties motivated the study developed here. A set of a reference material parameters for the adobe were obtained from a calibration of numerical models based on a quasi-static cyclic in-plane test on full-scale adobe wall representative of the typical Peruvian adobe constructions. The numerical modelling, within the micro and macro modelling approach, lead to a good prediction of the in-plane seismic capacity and of the damage evolution in the adobe wall considered.